General Rights and Obligations in the German Social Security Law - Thum, Matthias (University of Wroclaw. Faculty of Law, Administration & Economics, 2017)
Social rights are an important base for social peace within a society. Almost everybody in our modern western societies earns social benefits during his lifetime. The article discusses basic social rights and social duties by the public social administration and the residents, regulated in the general part of German social law. Both, duties and rights, are two sides of one medal. Duties of the administration are usually rights of the applicant and the other way round. The German Social Security Code No I (`Sozialgesetzbuch Erstes Buch, SGB I”) is a hand out by law for `best practice` in (public social) governance. The ideas of the SGB I can be a blueprint and ethics guideline for public administration.
Keywords: niemieckie prawo socjalne; prawa socjalne; obowiązki socjalne; publiczna administracja socjalna